1999
DOI: 10.1021/ie980384q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operating Variables on the Gas Holdup in a Large-Scale Slurry Bubble Column Reactor Operating with an Organic Liquid Mixture

Abstract: The effects of gas velocity, system pressure, and catalyst loading on gas holdup of H2, N2, CO, and CH4 in an organic mixture of hexanes were investigated in a 0.316 m diameter, 2.8 m height slurry bubble column reactor operating with a commercial Fischer−Tropsch iron-based catalyst. The data were obtained in the churn-turbulent flow regime with catalyst loading up to 50 wt % and a system pressure up to 8 bar. The hydrostatic pressure head method and the dynamic gas disengagement technique were employed to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 27 publications
10
34
0
Order By: Relevance
“…There have been several experimental studies reporting the gas holdup, e, and volumetric mass transfer coefficient, k L a, in slurry bubble columns. Most of these studies have reported experimental data on either e or k L a in slurry bubble columns; for literature surveys see Inga and Morsi [2] and Behkish et al [3]. In the present communication we have presented experimental data on both e and k L a.…”
Section: Introductionmentioning
confidence: 64%
“…There have been several experimental studies reporting the gas holdup, e, and volumetric mass transfer coefficient, k L a, in slurry bubble columns. Most of these studies have reported experimental data on either e or k L a in slurry bubble columns; for literature surveys see Inga and Morsi [2] and Behkish et al [3]. In the present communication we have presented experimental data on both e and k L a.…”
Section: Introductionmentioning
confidence: 64%
“…Ozturk et al [18] and Inga and Morsi [19] studied the effect of gas nature on the total gas holdup and reported that under similar pressure and superficial gas velocity, the gas holdups of CO 2 , air, N 2 , He and H 2 in xylene and those of H 2 , CO, N 2 and CH 4 in hexanes mixture, respectively appeared to follow the behavior of the molecular weight of the gas phase. Ozturk et al [18] investigated the effect of liquid nature on the gas holdup and showed that the gas holdups of various gases (CO 2 , air, N 2 , He and H 2 ) in several organic liquids were higher than those in water.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…This behavior is related to the fact that the increase of solid concentration can lead to the increase of slurry viscosity which promotes the formation of larger gas bubbles. Furthermore, if the pressure and gas velocity are maintained at constant level, the gas momentum per unit mass of slurry would decrease with increasing solid concentration and thus, the total gas holdup is expected to decrease with increasing solid amount [7]. The slurry viscosity seems to have a strong impact on the gas holdup [3,7].…”
Section: Resultsmentioning
confidence: 99%
“…For the commercial design or scale-up of the SBCR, an understanding of the characteristics such as mixing among gases, liquid and particles, gas holdup and heat and mass transfer in the SBCR are essential [5,6]. In addition, the flow behavior and characteristics of gas phase are known to play critical roles in determining the heat transfer coefficient, since the gas bubbles, which exist as a dispersed phase, are flowing stochastically and randomly in the viscous liquid as solvent with particles at high pressure [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%